News-Buffet: A Global News Aggregator for Real-Time, Location-Based Updates - Rajest, S. Suman; Regin, R. (Research Parks Publishing LLC, 2024)
Mobile devices have become indispensable instruments for staying current, thanks to the revolutionary change brought about by the rapid rise of technology. With an emphasis on giving users real-time access to worldwide news in an engaging and aesthetically pleasing format, this Android news app is meant to bring the latest news from more than 120 newspapers across 50+ countries. This app fills a need in the media application industry by providing quick access to news stories, which is becoming increasingly important as mobile internet usage continues to rise. One of the app's strongest points is how well it compiles and displays news stories from around the world. To keep the platform current and relevant, it has an admin interface for managing news that writers or admins can use to add, edit, or remove content. Also, users can get news stories that are particular to their area thanks to a module that uses their current location. This function, together with the app's built-in ad choices, shows how the app may be a great tool for brand marketing by letting companies advertise their wares within the news stories themselves. In order to guarantee the system's ongoing growth and relevance, this research application system conducts literature studies, market research, and comparative analysis to examine future development trends and strategies for media apps.